Resposta:
Explicació:
Del primer multiplicador,
Resposta:
Explicació:
# "tingueu en compte que per a x = 2" #
#2^3-6(2)^2+16=0#
#rArr (x-2) "és un factor" #
# "dividint" x ^ 3-6x ^ 2 + 16 "per" (x-2) #
#color (vermell) (x ^ 2) (x-2) color (magenta) (+ 2x ^ 2) -6x ^ 2 + 16 #
# = color (vermell) (x ^ 2) (x-2) color (vermell) (- 4x) color (magenta) (- 8x) + 16 #
# = color (vermell) (x ^ 2) (x-2) color (vermell) (- 4x) color (vermell) (- 8) (x-2) cancel·lació (color (magenta) (- 16)) cancel·la (+16) #
# rArrx ^ 3-6x ^ 2 + 16 = 0 #
#rArr (x-2) (x ^ 2-4x-8) = 0
# "resol" x ^ 2-4x-8 "utilitzant el" color (blau) "fórmula quadràtica" #
# "amb" a = 1, b = -4 "i" c = -8 #
# x = (4 + -sqrt (16 + 32)) / 2 #
#color (blanc) (x) = (4 + -sqrt48) / 2 = (4 + -4sqrt3) / 2 = 2 + -2sqrt3 #
#rArr (x-2) (x ^ 2-4x-8) = 0
# "té solucions" x = 2, x = 2 + -2sqrt3 #